GLOBAL EVIDENCE ON RISK FACTORS FOR CHILDHOOD TUBERCULOSIS: A SCOPING REVIEW - Safira, Rahma; Setyawan, Henry; Hadisaputro, Suharyo (Jambura Journal of Health Sciences and Research, 2025)
Childhood tuberculosis (TB) remains a major global public health concern, particularly in developing countries, due to children’s immature immune systems and frequent exposure to infectious adults within households. This scoping review aimed to identify and synthesize global evidence on risk factors associated with TB among children aged 0–19 years, following the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines. Unlike previous systematic reviews that focused on specific regions or populations, this study comprehensively mapped risk factors using evidence from PubMed, Scopus, and Garuda databases up to March 2025. Eleven primary studies meeting the inclusion criteria were analyzed thematically. The most frequently reported risk factors included close contact with adult TB patients, lack of Bacillus Calmette–Guérin (BCG) vaccination, malnutrition, overcrowded housing, and poor ventilation. Additional factors such as HIV infection, exposure to cigarette smoke, low parental education, and poor household income further increased susceptibility. The findings indicate that childhood TB arises from a complex interplay of biological, social, and environmental determinants. Therefore, effective prevention strategies should integrate immunization, active contact tracing, family health education, and improvement of living conditions. This review provides valuable insights for strengthening community-based TB control programs, highlights the need to prioritize children as a vulnerable population, and identifies research gaps to guide future policy and interventions toward TB elimination.